Inactivation of TMEM106A promotes lipopolysaccharide-induced inflammation via the MAPK and NF-κB signaling pathways in macrophages. (23rd October 2020) - Zhang, X; Feng, T; Zhou, X; Sullivan, P M; Hu, F; Lou, Y; Yu, J; Feng, J; Liu, H; Chen, Y
Summary: Pattern recognition receptors, such as Toll-like receptors (TLRs), play an important role in the host defense against invading microbial pathogens. Their activation must be precisely regulated, as inappropriate activation or overactivation of TLR signaling pathways may result in inflammatory disorders, such as septic shock or autoimmune diseases. TMEM106A is a type II transmembrane protein constitutively expressed in macrophages. Our current study demonstrated that TMEM106A levels were increased in macrophages upon lipopolysaccharide (LPS) stimulation, as well as in the peripheral monocytes of patients with sepsis. Tmem106a knockout mice were more sensitive to lipopolysaccharide (LPS)-induced septic shock than wild-type mice. Further experiments indicated that Tmem106a ablation enhanced the expression of CD80, CD86 and major histocompatibility complex (MHC)-II in mouse macrophages upon LPS stimulation, accompanied with up-regulation of tumor necrosis factor (TNF)-α, interleukin (IL)-6, interferon (IFN)-β and inducible nitric oxide synthase (iNOS), indicating the activation of macrophages and polarization towards the M1 inflammatory phenotype. Moreover, elevated mitogen-activated protein kinase (MAPK) and nuclear factor kappa B (NF-κB) signaling were found to be involved in the LPS-induced inflammatory response in Tmem106a −/− macrophages. However, this effect was largely abrogated by macrophage deletion in Tmem106a −/− mice. Therefore, deficiency of Tmem106a in macrophages may enhance the M1 polarization in mice, resulting in inflammation. This suggests that TMEM106A plays an important regulatory role in maintaining macrophage homeostasis. Graphical Abstract: